2013
DOI: 10.1038/ncomms2699
|View full text |Cite
|
Sign up to set email alerts
|

High-coherence picosecond electron bunches from cold atoms

Abstract: Ultrafast electron diffraction enables the study of molecular structural dynamics with atomic resolution at subpicosecond timescales, with applications in solid-state physics and rational drug design. Progress with ultrafast electron diffraction has been constrained by the limited transverse coherence of high-current electron sources. Photoionization of laser-cooled atoms can produce electrons of intrinsically high coherence, but has been too slow for ultrafast electron diffraction. Ionization with femtosecond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 30 publications
1
72
0
Order By: Relevance
“…[20][21][22] At the moment, these sources are primarily intended for the use in electron diffraction experiments on molecules. 37 As the electron energies are progressively lowered, effects of resonant scattering such as discussed here should become observable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] At the moment, these sources are primarily intended for the use in electron diffraction experiments on molecules. 37 As the electron energies are progressively lowered, effects of resonant scattering such as discussed here should become observable.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Particularly relevant to the present treatment is the rapid development of highly coherent sources of cold electrons. [20][21][22] Cold-atom collisions can also be studied in the time domain. Boesten et al 23 have observed the time dependence of a cold-atom collision in a pulsed photoassociation experiment.…”
Section: Introductionmentioning
confidence: 99%
“…In the same region, the emittance from the CW excitation laser was 141 ± 7 nm. Though the femtosecond emittance is larger, the corresponding coherence length is still relatively large for an electron source, at L c = 4.0 ± 0.2 nm [16].…”
Section: Ultra-fast Cold Electronsmentioning
confidence: 99%
“…With femtosecond excitation, the initial electron pulse duration is limited by the spatial and temporal extent of the overlap between the new femtosecond pulses and the 5 ns pulses of 480 nm light. The overlap produces a shaped pulse of electrons or ions with a minimum duration of 150 ps [16]. The high bandwidth inherent to short laser pulses might be expected to increase the excess energy spread of the electrons and thus destroy their transverse coherence.…”
Section: Ultra-fast Cold Electronsmentioning
confidence: 99%
See 1 more Smart Citation